Transportable energy storage for more resilient distribution systems with multiple microgrids - Yao, Shuhan (2019)
Transportable energy storage systems (TESSs) have great potential to enhance resilience of distribution systems (DSs) against large area blackouts. A joint post-disaster restoration scheme for TESS and generation scheduling in microgrids (MGs) and network reconfigurations is proposed to minimize the total system cost, including customer interruption cost, generation cost, and TESS related costs. A temporal-spatial TESS model which is related to both transportation networks and DSs is proposed to represent the difference between TESS and ESS in terms of flexibility and cost reduction of ESS sharing among MGs. The proposed restoration problem is formulated as a mixed-integer linear programming with considering various network and TESS constraints. The proposed model and scheme are tested in a modified 33-bus test system with three MGs and four TESSs. The results verify that a distribution system with TESS is more resilient compared with conventional ESS because of the benefit from total cost reduction.